CHINESE MUSLIM SUBCULTURE: CULTURE AND RELIGIOUS INTEGRATION IN SEMARANG'S MULTICULTURAL SOCIETY - Musaffa, Muhamad Ulul Albab; Taufiqurohman, Taufiqurohman; Abdurrahman, Landy Trisna; Muhyidin, Muhyidin (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2025)
AbstractWithin the landscape of Indonesia’s ethnic and religious diversity, the Chinese Muslim community in Semarang occupies a unique position as a “minority within a minority,” navigating sociocultural pressures from the non-Muslim Chinese milieu and the predominantly Javanese Muslim majority. Located in a city shaped by centuries of Sino-Javanese interaction, the community’s lived experience offers valuable insight into the harmonious coexistence of cultural heritage and Islamic values. This study examines how identity preservation and da‘wah strategies are negotiated within this context, drawing on in-depth interviews, participant observation, and document analysis. Employing Dick Hebdige’s subcultural theory, this study finds that the community actively incorporates Chinese cultural symbols such as language, rituals, and traditional festivals into inclusive da‘wah practices. Through such integrative approaches, the community resists cultural erasure while simultaneously promoting social cohesion. This study highlights the potential of culturally embedded religious practices to strengthen interfaith dialogue, enhance public understanding of diversity, and inform policy frameworks for minority integration. By situating the lived experiences of Chinese Muslims within broader discourses on multiculturalism and interfaith harmony, the study contributes to a deeper understanding of hybrid identities as a foundation for inclusive and resilient societies in Indonesia and across Southeast Asia. AbstrakDalam lanskap keberagaman etnis dan agama di Indonesia, komunitas Muslim Tionghoa di Semarang menempati posisi unik sebagai “minoritas dalam minoritas,” yang harus menghadapi tekanan sosiokultural dari lingkungan Tionghoa non-Muslim sekaligus mayoritas Muslim Jawa. Berada di sebuah kota yang dibentuk oleh interaksi Tionghoa-Jawa selama berabad-abad, pengalaman hidup komunitas ini memberikan wawasan berharga mengenai koeksistensi harmonis antara warisan budaya dan nilai-nilai Islam. Studi ini menelaah bagaimana strategi pelestarian identitas dan dakwah dinegosiasikan dalam konteks tersebut, dengan menggunakan wawancara mendalam, observasi partisipan, dan analisis dokumen. Dengan memanfaatkan teori subkultural Dick Hebdige, studi ini menemukan bahwa komunitas secara aktif mengintegrasikan simbol-simbol budaya Tionghoa—seperti bahasa, ritual, dan perayaan tradisional—ke dalam praktik dakwah yang inklusif. Melalui pendekatan integratif ini, komunitas mampu melawan penghapusan budaya sekaligus mendorong kohesi sosial. Studi ini menyoroti potensi praktik keagamaan yang berakar pada budaya untuk memperkuat dialog antaragama, meningkatkan pemahaman publik tentang keberagaman, dan memberikan kontribusi pada kerangka kebijakan integrasi minoritas. Dengan menempatkan pengalaman hidup Muslim Tionghoa dalam wacana yang lebih luas tentang multikulturalisme dan harmoni antaragama, studi ini memperkaya pemahaman tentang identitas hibrida sebagai fondasi bagi masyarakat yang lebih inklusif dan tangguh di Indonesia maupun Asia Tenggara.